2016
DOI: 10.5194/tc-10-535-2016
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of long-term series of glaciological and geodetic mass balance for 10 Norwegian glaciers

Abstract: Abstract. Glaciological and geodetic methods provide independent observations of glacier mass balance. The glaciological method measures the surface mass balance, on a seasonal or annual basis, whereas the geodetic method measures surface, internal, and basal mass balances, over a period of years or decades. In this paper, we reanalyse the 10 glaciers with long-term mass-balance series in Norway. The reanalysis includes (i) homogenisation of both glaciological and geodetic observation series, (ii) uncertainty … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
117
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(129 citation statements)
references
References 38 publications
11
117
1
Order By: Relevance
“…are available (Andreassen et al, 2016). The discrepancy between new and old outlines are minor and do not influence the results presented in this paper.…”
Section: Additional Datamentioning
confidence: 72%
“…are available (Andreassen et al, 2016). The discrepancy between new and old outlines are minor and do not influence the results presented in this paper.…”
Section: Additional Datamentioning
confidence: 72%
“…In addition and according to Andreassen et al (2016), we assume that the extrapolation over areas not covered by point 150 measurements inherits uncertainties of ±0.10 m w.e. a -1 .…”
Section: The Glaciological Methodsmentioning
confidence: 99%
“…Several studies have shown that basal and internal melt can be important contributors to total glacier ablation, depending on the specific glacier and the climatic setting (e.g., Alexander et al, 2011;Oerlemans, 2013;Andreassen et al, 2016). Generally, the most important sources of energy for subsurface melt on temperate glaciers are related to the conversion of potential energy by water runoff inside and at the base of the glacier.…”
Section: The Role Of Basal and Internal Meltmentioning
confidence: 99%
“…For this reason we clearly flag all results related to modeling and provide full methodical transparency in order to enable possible data users to decide whether the data suit their purpose or not. The applied model was run in its point configuration as the purpose of this study is not to use a model for the spatial extrapolation of point measurements on the glacier-wide scale as done in a number of other studies Barandun et al, 2015;Kronenberg et al, 2016;Sold et al, 2016) but is rather to reproduce a best possible estimate of annual balance values for point locations where ablation stakes were placed in the subsequent years. In this configuration, the model performance can be validated directly using data from available stake measurements.…”
Section: Point Mass Balance Modelingmentioning
confidence: 99%
See 1 more Smart Citation